Did early-career complexity increase after labour market deregulation? Heterogeneity by gender and education across cohorts in Italy - Emanuela Struffolino; Michele Raitano (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2019)
This article considers the complexity of ea rly employment life-courses focusing on the heterogeneity by gender and education. We construct 7-year-long early employment trajectories by using a unique longitudinal da taset that combines administrative records on employment episodes and survey data from the Italian module of the EU-SILC. This enables the application of advanced method s in sequence analysis to calculate the complexity of employment trajectories following labour market entry. Complexity reflects the instability of early-careers by consid ering the number of transitions between employment states and the length of each epis ode. We compare several cohorts of Italian workers who entered the labo ur market between 1974 and 2001 in institutional contexts characterized by different levels of deregu lation. The results demonstrate that early-career complexity increased across cohorts, but mostly for medium and lower-educated individuals. This dynamic is particularly pr onounced for women, and complexity is the highest for recent cohorts, especially among those with less human capital.
Keywords: 300; labour market; youth; gender; education; flexibility; sequence analysis